Analisa Dampak Non-Performing Financing Terhadap Pembiayaan Pada PT Bank Syariah Indonesia Tbk. - Zidan Fahrezi; Yoko Tristiarto (Islamic Economics and Business Review, 2025)
This study aims to determine the impact of non-performing financing (NPF) on financing distribution at PT Bank Syariah Indonesia Tbk. (BSI). The writing method used is descriptive quantitative with comparative analysis techniques and time series index analysis using the NPF-gross ratio. The results of the analysis show that NPF-gross is correlated with financing distribution at PT Bank Syariah Indonesia Tbk. Based on the contract, with a smaller NPF ratio, murabahah, musyarakah, and qardh become the three contracts with the largest financing distribution at BSI, while istishna becomes the contract with the smallest distribution at BSI. NPF at BSI is included in the healthy category because BSI's NPF is below the maximum limit stipulated by Bank Indonesia in NPF, which is 5%. The limitation of this study is that the NPF-nett ratio is not used to see whether the NPF ratio has an impact on financing distribution at BSI. Another limitation is the exclusion of other variables, such as CAR and Third Party Funds (DPK), which are suspected of impacting financing disbursement at BSI. This study offers novelty because it addresses all financing disbursement contracts, not limited to those commonly used in previous studies, such as mudharabah and musyarakah, allowing for a broader overview of financing contracts. Keywords: Financing; Financing Contract; Financing Risk; Non-Performing Financing; Resolving Financing Problems